Binary Option Affiliate Mode in Money Laundering - Paradise, Moh. Iqbal; Fatoni, Syamsul (Nursyam Centre, 2023)
This article aims to analyze the legal arrangements regarding money laundering under the guise of binary options trading and the elements behind the actions of binary option affiliates can be qualified as money laundering crimes. This study discusses regulations related to money laundering under the guise of binary options trading and the elements behind the actions of binary option affiliates can be qualified as money laundering crimes. The type of research is normative, with a statutory approach and a case approach, legal material collection techniques consisting of literature studies, document studies, and online research as well as methods of descriptive legal material analysis and deductive conclusion making. The results showed that the regulation of money laundering in the mode of binary options trading in Indonesia is regulated in Article 3 of the TPPU Law, while the mode of binary options trading itself is regulated in Article 378 of the Criminal Code concerning fraud, Article 27 paragraph (2) and article 28 paragraph (1) of the ITE Law. While the elements behind the actions of binary option affiliates can be qualified as money laundering crimes are the existence of original crimes, namely fraud and online gambling and the act of disguising assets obtained from the results of binary option affiliates by spending these assets and giving them free of charge to others in unreasonable large amounts, As well as storing them in the form of digital assets such as crypto and bitcoin